"scuri boschi, in luoghi strani e inculti": The Literary Afterlives of Dante’s Wood of the Suicides in the Italian Renaissance - Barlow, Emma Louise (Spunti e Ricerche, 2022)
The reception and reconceptualization of Dante’s depiction of suicide in the Commedia is an understudied aspect of his legacy. Through close textual analysis of Dante’s Commedia and a comparative analysis with early modern Italian poetry and prose, this study examines the adoption and adaptation of Dante’s arboreal imaginary of suicide and explores both the ways in which the literary Renaissance engaged with the rich symbols that Dante associates with suicide, and the potentially obscured meanings of those symbols. The study contributes to a broader understanding of how suicide has been considered and discussed in different historical periods, and as such hopes to further dissolve the taboos that surround the subject